Interdisciplinarity for sale: Logics of knowledge, labour markets and consumerism. (21st October 2018) - Pizarro Milian, Roger; Missaghian, Rod
Abstract: Interdisciplinary programmes have proliferated across post‐secondary education in recent decades. Despite this, little attention has been paid to the manner in which interdisciplinary programmes promote themselves to external constituents. To study this process, we conduct a content analysis of the online self‐descriptions of 203 credential‐granting interdisciplinary programmes across the Canadian university sector. We find that these entities embrace contrasting logics of superior knowledge, labour market outcomes and customisation. We interpret these findings through the lens of contemporary theorising within organisation studies, noting that their ambidexterity bodes well for their continued existence within the sector.